用因式分解法解下列方程 (1) 1\3x^2+3\8x+4=0 (2) (x-3)(x+2)=6
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 10:46:06
用因式分解法解下列方程(1)1\3x^2+3\8x+4=0(2)(x-3)(x+2)=6用因式分解法解下列方程(1)1\3x^2+3\8x+4=0(2)(x-3)(x+2)=6用因式分解法解下列方程(
用因式分解法解下列方程 (1) 1\3x^2+3\8x+4=0 (2) (x-3)(x+2)=6
用因式分解法解下列方程 (1) 1\3x^2+3\8x+4=0 (2) (x-3)(x+2)=6
用因式分解法解下列方程 (1) 1\3x^2+3\8x+4=0 (2) (x-3)(x+2)=6
(1) 1\3x^2+3\8x+4=0
两边乘8
x²+3x+32=0
显然无解
(2) (x-3)(x+2)=6
x²-x-6=6
x²-x-12=0
(x+3)(x-4)=0
x=-3,x=4
1
不会
2 x方减去x减去6=6
x方减去x=0
x(x-1)=0
所以,x=1
x=0
(x+3)(x-1)=5 用因式分解法解下列方程
用因式分解法解下列方程:(2X-1)²=(3-X)²
用因式分解法解下列方程...急!用因式分解法解下列方程x²+3=3(x+1)
用因式分解法解下列方程(x+3)²=9(1-2x)²
用因式分解法解下列方程:(x十1)(x一3)=0
用因式分解法解下列方程:4(3x+1)^2-9=0
用因式分解法解下列方程:(1+x)^2-9=0
用因式分解法解下列方程 3x²(x-1)=2(x-|)
用因式分解法解下列方程(1)(3x+1)²-4x²=0
用因式分解法解下列方程(2X+1)+3(2X+1)+2=0
用因式分解法解下列方程(5x-1)2=3(5x-1)
用因式分解法解下列方程(1)(3x+2)²-4x²=0
用因式分解法解下列方程3(x-3)=(x-3)²
用因式分解法解下列方程 (x-3)=3-x
用因式分解法解下列方程 x(x-2)=3
用因式分解法解下列方程 4x²-4x+1=0
用因式分解法解下列方程:4X⑵-(X-1)⑵=0
用因式分解法解下列方程(x-5)²=2(x-5)-1